Pourquoi, quoi, comment… et après ? Regards de chercheure et d’enseignant sur un projet collaboratif en éducation autochtone - Eva Lemaire; René Beauparlant; Cécile Howse (Recherches en didactique des langues et des cultures)
In this article2, grounded into the Canadian context and into the ongoing reconciliation process between Indigenous and non-Indigenous Peoples, our intent is to discuss a collaborative research involving both a Métis Elder and a group of school teachers. On the one hand, we discuss the complementarities and practicalities implied by the collaboration between the researcher and a specific teacher involved in the research. On the other end, we discuss how the researcher can support building a bridge between local school and Indigenous communities. This text aims to highlight a few complex articulations between teacher and academic knowledge, as well as between Western and Indigenous postures, emphasizing the principle of complementarity and the importance of ethical practices.